ANALISIS PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA PADA PROYEK KONSTRUKSI GEDUNG BERTINGKAT TINGGI - Yuliana, Ida (Universitas Muhammadiyah Palembang, 2021)
The implementation of safety and health management system (SMK3) in the construction world is currently a must, given the large number of workers involved and the workplace that has a high risk of work accidents. The SS apartment development project in Bandung is one of the high-rise building construction projects carried out by the WGG contractor. The implementation of HSE on construction projects by the contractor is carried out in the context of controlling risks related to work activities in order to create a safe, efficient and productive workplace. This study aims to assess the level of application (SMK3) on the SS apartment project in the city of Bandung. The research method used is descriptive qualitative method with data collection in the form of checklist observations and interviews based on government regulation number 50 of 2012 (PP Nomor 50 tahun 2012). The results show that the implementation of SMK3 by contractors in this SS apartment project reaches a value of 89.66% which means the level of achievement of SMK3 implementation in the project. it falls into the satisfactory category.Key Words : SMK3, HSE, apartment, interviews